Urban Sustainability in Practice: Analyzing the Implementation of the Low-Carbon City Program in Makassar - Sadid Parassa, Helni; Sari, Jayanti Armida; Mujtahid, Iqbal Miftakhul; Sandi, Fadri Ari; Putro, Yusup Lintang Cahyo Andrian (JAKPP (Jurnal Analisis Kebijakan & Pelayanan Publik), 2025)
The Indonesian government, through Law Number 32 of 2009, emphasizes that a good and healthy environment is a fundamental right of every citizen. Various efforts have been made, including the development of regulations, the "Blue Sky" program, and the use of alternative fuels to reduce air pollution.The city of Makassar, through Regional Regulation Number 4 of 2015 concerning the Makassar City Spatial Plan 2015–2034, integrates concepts such as low-carbon city, green city, and climate mitigation city to create a more comfortable and less polluted environment.This study aims to analyze the implementation of the "Low Carbon City" program in Makassar. Using Van Meter & Van Horn's (1975) theoretical framework with a mixed methods research approach, the findings indicate that in early 2024, the Makassar city government focused on carbon emission reduction by promoting the low-carbon city program. The city government collaborates with universities and NGOs in implementing this initiative. While some programs have already been implemented and others are still in progress, a lack of public awareness campaigns has resulted in low public awareness of the program. Additionally, leadership changes at the local level are feared to hinder the sustainability of the initiative.